The effectiveness study of cockle shell in treating acidic surface water - Nurul Ain, Zainodin (2012)
Malaysia was reported to produce 13,000 metric ton of cockle shell during Ninth Malaysia Plan (2006-2010). In 2007, Malaysia has a number of 1055 of farmers working on cockle cultivation agriculture with 6000 hectare of cultivation area (lzura, 2008). These figures do not only indicate the vast availability of cockles but also the amount of waste generated. This project was run in attempt to study the potential of cockle shell in ameliorating surface water acidification. A lab-scale study of different sizes and volumes of cockle shell and limestone was used. The values of pH were measured continuously at interval time until the pH remains constant. The effectiveness of cockle shell to increase the pH of acidic water to circum-neutral was then compared to limestone. Thus, it is believed that the cockle shell would be able to replace limestone in liming process. Moreover, the availability of cockle is high and low cost.